Bilateral Flexor Digitorum Accessorius Longus Precipitating Bilateral Tarsal Tunnel Syndrome: A Case Report. Issue 2 (6th April 2023) - Propp, Bennett E.; Torre, Barrett B.; Bellas, Nicholas; Sathe, Vinayak
Abstract : Case: A 29-year-old woman presented with bilateral tarsal tunnel syndrome caused by bilateral flexor digitorum accessorius longus, experiencing immediate relief of symptoms after surgical intervention through 1 year. Conclusion: Accessory muscles can cause compressive neuropathies in multiple areas of the body. In patients who have FDAL as the cause of their tarsal tunnel syndrome, surgeons should have a high index of suspicion of bilateral FDAL if the same patient develops similar contralateral symptoms.